Analysis Of Science Literacy Skills Of Grade IV Students On Material Changes In The Form Of Objects - Rismayanti; Makki, Muhammad; Nurwahidah; Syazali, Muhammad (Mataram University, 2024)
This study aims to describe the science literacy ability of grade IV students in the aspect of knowledge and competency in the material of changing the form of objects at SDN 39 Cakranegara. This study uses a descriptive qualitative approach with the type of case study research. The data source in this study is teachers and students of grade IV of SDN 39 Cakranegara which totals 21 students and one teacher. The data collection method used was in the form of a written test distributed into 20 multiple-choice questions and 5 essay questions and semistructural interviews. Data analysis was carried out based on the Miles, Huberman and Saldana model with analysis steps, namely: data collection, data condensation, data presentation and conclusion drawn. Data analysis was carried out on 10 grade IV students based on the category of obtaining science literacy scores in the high, medium, low, and very low categories. The results of the study showed that the overall results of the science literacy ability test in grade IV at SDN 39 Cakranegara based on the results of the analysis obtained an average of 52.27 with a very low category. Science literacy ability based on the level of science literacy ability in the knowledge aspect and competency aspect is categorized into very high, high, medium, low and very low criteria. In the aspect of knowledge and the competency aspect of students in the high category, there are indicators of the ability to explain scientific phenomena and indicators of the ability to interpret scientific data and evidence. In the medium category, there are indicators of the ability to interpret data and scientific evidence. In the low category, there are indicators of knowledge of content and indicators of the ability to evaluate scientific data and evidence, and in the very low category, there are indicators of the ability to evaluate and design scientific investigations.